Phase time delay and Hartman effect in a one-dimensional photonic crystal with four-level atomic defect layer. Issue 14 (6th August 2017) - Jamil, Rabia; Ali, Abu Bakar; Abbas, Muqaddar; Badshah, Fazal; Qamar, Sajid
Abstract: The Hartman effect is revisited using a Gaussian beam incident on a one-dimensional photonic crystal (1DPC) having a defect layer doped with four-level atoms. It is considered that each atom of the defect layer interacts with three driving fields, whereas a Gaussian beam of width w is used as a probe light to study Hartman effect. The atom–field interaction inside the defect layer exhibits electromagnetically induced transparency (EIT). The 1DPC acts as positive index material (PIM) and negative index material (NIM) corresponding to the normal and anomalous dispersion of the defect layer, respectively, via control of the phase associated with the driving fields and probe detuning. The positive and negative Hartman effects are noticed for PIM and NIM, respectively, via control of the relative phase corresponding to the driving fields and probe detuning. The advantage of using four-level EIT system is that a much smaller absorption of the transmitted beam occurs as compared to three-level EIT system corresponding to the anomalous dispersion, leading to negative Hartman effect.